Sebuah Rekonseptualisasi Kesejahteraan Regional: Paradigma 'Pro-Pertumbuhan' dan 'Pasca-Pertumbuhan' dalam Perencanaan Pembangunan: Kajian Literatur Sistematis dan Kerangka Konseptual - LUTHFI AZHARI; HAFIZ MAULANA; ERWIN ANANDA; MARSELINUS FIARDI; ANGELIQUE CALLISTA PUTRI LEVINA (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2026)
Regional development planning faces a debate between the 'pro-growth' paradigm (GDP-focused) and the 'post-growth' paradigm (holistic well-being and ecological limits). The 'pro-growth' approach is criticized for causing environmental degradation and social inequality. This study aims to identify the characteristics, analyze the implications, and develop a conceptual framework integrating both paradigms. Using a Systematic Literature Review (SLR) method, 59 articles from Scopus, Web of Science, and ScienceDirect were thematically analyzed. Findings show that 'pro-growth' leads to environmental degradation and inequality , while 'post-growth'öfocusing on justice and local resilienceöfaces implementation challenges like political resistance and the need to redefine prosperity. The study concludes that regional prosperity must transcend GDP. Its primary contribution is a new conceptual framework bridging both paradigms to achieve holistic, resilient, and sustainable regional prosperity. Keywords: Development Planning, Regional Development, Pro-Growth, Post-Growth, Systematic Literature Review, Conceptual Framework.